PENGEMBANGAN VIDEO PEMBELAJARAN MENULIS PUISI UNTUK SISWA KELAS V SEKOLAH DASAR - Zubaidah, Siti; Wiryotinoyo, Mujiyono; Sudaryono, Sudaryono (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2014)
Media that had been used at the time of learning to write poetry is to wear textbooks and worksheets, although using the environment and even then only in the classroom. The school has actually set up a computer and digital projector; the facility cannot be fully utilized due to the limited ability of the teacher. Armed with the help of video learning process more interesting and meaningful. Besides video media is used as an important learning to cope with students' learning styles, both students who have a visual learning style and learning style audio. Their lessons can be combined with the use of information technology advances. Through the advancement of the teachers can use video. This results in a product development research video for learning to write poetry. The specifications of the products developed by the researchers contains a step -by-step how to write poetryand poetry is equipped with a visualization exercise for the task of writing poetry . Keyword: Video learning, writing poetry